29 Does tongue reduction surgery affect Sleep Disordered Breathing in patients with Beckwith-Wiedemann Syndrome?. (22nd November 2019) - Godinho, Ansel; Russo, Kylie; Laverty, Aidan; Abel, Francois; Ong, Juling; Samuels, Martin
Abstract : Introduction: Beckwith-Wiedemann Syndrome (BWS) is a congenital condition where patients have macroglossia, often requiring tongue reduction surgery as well as being a potential risk factor for obstructive sleep apnoea (OSA). Prevalence of OSA is high and therefore sleep studies (SS) pre- and post-surgery are useful to assess the impact of surgery. Method: From 58 patients with BWS who underwent SS before or after tongue reduction surgery over a 20-year period, there were 9 patients who had tongue reduction surgery plus a SS pre- and post-operatively with sufficient data to calculate an Apnoea Hypopnoea Index (AHI). Results: Figure 1 shows the change in Obstructive AHI (OAHI) before and after tongue reduction surgery in the 9 patients. Discussion: In our cohort with pre- and post-surgery SS data the prevalence of OSA was 44% (mild: 100%). 4 patients showed reductions in OAHI after surgery (mean change: 1evs/hr), 3 others showed a worsening (mean change: 5.5evs/hr), while 2 showed no change in OAHI. Of the 3 that worsened, 1 was restudied after two years and showed no evidence of OSA with no medical intervention. Another had grade 2 tonsils which have been surgically removed. The third patient is waiting for ENT surgical review. The small sample size of BWS patients with sufficient SS to qualify for this study may be related to the referral pathway with the majority of patients diagnosed with moderate to severe OSA pre- surgery were either treated (e.g. tracheostomy) or surgery delayed due to OSA. In conclusion, tongue reduction surgery does not appear to affect the level of OSA and patients who had worsening of OSA, had other factors in their history predominantly ENT related. An alternative method of assessment, such as a questionnaire, focussed on sleep disordered breathing, might be a better determinant of the impact of surgery.